2y(3)-x(2)=

Simple and best practice solution for 2y(3)-x(2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y(3)-x(2)= equation:


Simplifying
2y(3) + -1x(2) = 0

Reorder the terms for easier multiplication:
2 * 3y + -1x(2) = 0

Multiply 2 * 3
6y + -1x(2) = 0

Reorder the terms for easier multiplication:
6y + -1 * 2x = 0

Multiply -1 * 2
6y + -2x = 0

Reorder the terms:
-2x + 6y = 0

Solving
-2x + 6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-2x + 6y + -6y = 0 + -6y

Combine like terms: 6y + -6y = 0
-2x + 0 = 0 + -6y
-2x = 0 + -6y
Remove the zero:
-2x = -6y

Divide each side by '-2'.
x = 3y

Simplifying
x = 3y

See similar equations:

| (2x-10)/(x^2-25)=1/x | | 6.5=2.5(7)-11 | | 2y(3)-2= | | -22=-10-12 | | 3(x+2)-2(x+4)=7 | | .25(x)=1500 | | .25x+x=1500 | | (3n/8)-(n/12)=-(7/6) | | 2(X-2)+7=2(X+5) | | x^3-2x+8x+2x^2+5x+x^3+2x^2-3x-3= | | 3x^3+2x=3 | | 5/2/10/4=50/n | | 0.13-0.001(x+1)=-00.3(4-x) | | 3x^3-2x+8x= | | 1.25x^2-9x-16=0 | | 3(3n+3)=6(4n+6)+6 | | 2(-6x-18/7) | | 14/5/1/5=49/2/7/6 | | n/50=2/100 | | -3(2x-1)+7=-6x+10 | | 2a+8=6 | | 5x-25=x+75 | | t=27-1/2(w-k) | | (x-1)=x-1 | | 5(4x-1)=20x-5 | | 15/5/3=50/n | | 0.10(y-6)+0.33y=0.03y-0.40 | | 7+0.25r=-17 | | 0.72+0.24t=2.64t-0.72 | | -25=0.2h+5 | | 1.8x+2.8=2.5+21 | | 0.5j+4=-15 |

Equations solver categories